The Evolving Role of Women in Contemporary Indonesian Da'wah - OMANG KOMARUDIN, Omang (EDUTEC : Journal of Education And Technology, 2025)
Since the advent of Islam, women have played a significant role in shaping social and religious dynamics, epitomized by figures like Khadijah bint Khuwaylid. This study employs a qualitative library research method, utilizing content and thematic analysis of relevant literature, to explore the patterns and implications of women's roles in contemporary Islamic preaching (da'wah) from a gender studies perspective. Using Indonesia as a case study, the research investigates how communication strategies in da'wah shape religious beliefs and behaviors. The findings reveal that while traditional structures often limit women to supportive roles, the rise of digital platforms and female leadership in Muslim-majority countries has facilitated a significant shift. The analysis identifies three key themes: the reclamation of female Islamic scholarship, the use of social media for creating inclusive religious narratives, and the strategic negotiation of gender norms within religious discourse. The study concludes that empowering women in da'wah is crucial not only for gender equity but also for fostering a more dynamic and responsive Islamic discourse in the modern era, offering a critical framework for understanding the evolving agency of Muslim women in religious spheres